2010
DOI: 10.1007/s00436-010-2065-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting patterns of tick parasitism on forest rodents in tick-borne encephalitis risk areas, Germany

Abstract: Identifying factors affecting individual vector burdens is essential for understanding infectious disease systems. Drawing upon data of a rodent monitoring programme conducted in nine different forest patches in southern Hesse, Germany, we developed models which predict tick (Ixodes spp. and Dermacentor spp.) burdens on two rodent species Apodemus flavicollis and Myodes glareolus. Models for the two rodent species were broadly similar but differed in some aspects. Patterns of Ixodes spp. burdens were influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
85
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 41 publications
16
85
4
Order By: Relevance
“…Our results regarding intrinsic factors are consistent with previous studies, which showed higher tick burdens on males compared to females 215 , an increase in tick burden with increasing body mass of the host 95,215 and higher tick burdens on Apodemus mice compared to Bank voles 89,95 . These differences have been attributed both to differences in day range between host individuals 215 and differences in resistance against or tolerance for parasites between host species 13,23 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results regarding intrinsic factors are consistent with previous studies, which showed higher tick burdens on males compared to females 215 , an increase in tick burden with increasing body mass of the host 95,215 and higher tick burdens on Apodemus mice compared to Bank voles 89,95 . These differences have been attributed both to differences in day range between host individuals 215 and differences in resistance against or tolerance for parasites between host species 13,23 .…”
Section: Discussionsupporting
confidence: 92%
“…These differences have been attributed both to differences in day range between host individuals 215 and differences in resistance against or tolerance for parasites between host species 13,23 . Our results regarding extrinsic factors (deer and predator abundance, and rodent density) are also consistent with previous studies, which Determinants of Tick Burden on Rodents | 89 found an increase in larval burden on rodents with increasing deer density 32 and a decreasing larval burden with increasing rodent density 95,227 . However, we are the first to report a decrease in tick burden with increasing relative abundance of predators.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations